Hippocampal neural disinhibition causes attentional and memory deficits - McGarrity, Stephanie; Mason, Rob; Fone, Kevin C.F.; Pezze, Marie A.; Bast, Tobias (Oxford Journals, 2017)
Subconvulsive hippocampal neural disinhibition, that is reduced GABAergic inhibition, has been implicated in neuropsychiatric disorders characterized by attentional and memory deficits, including schizophrenia and age-related cognitive decline. Considering that neural disinhibition may disrupt both intra-hippocampal processing and processing in hippocampal projection sites, we hypothesized that hippocampal disinhibition disrupts hippocampus-dependent memory performance and, based on strong hippocampo-prefrontal connectivity, also prefrontal-dependent attention. In support of this hypothesis, we report that acute hippocampal disinhibition by microinfusion of the GABA-A receptor antagonist picrotoxin in rats impaired hippocampus-dependent everyday-type rapid place learning performance on the watermaze delayed-matching-to-place test and prefrontal-dependent attentional performance on the 5-choice-serial-reaction-time test, which does not normally require the hippocampus. For comparison, we also examined psychosis-related sensorimotor effects, using startle/prepulse inhibition (PPI) and locomotor testing. Hippocampal picrotoxin moderately increased locomotion and slightly reduced startle reactivity, without affecting PPI. In vivo electrophysiological recordings in the vicinity of the infusion site showed that picrotoxin mainly enhanced burst firing of hippocampal neurons. In conclusion, hippocampal neural disinhibition disrupts hippocampus-dependent memory performance and also manifests through deficits in not normally hippocampus-dependent attentional performance. These behavioral deficits may reflect a disrupted control of burst firing, which may disrupt hippocampal processing and cause aberrant drive to hippocampal projection sites.